Recent advances in the treatment of advanced or recurrent endometrial cancer. (September 2009) - Crosbie, Emma J; Kitchener, Henry C
Advanced or recurrent endometrial cancer is relatively uncommon and carries a poor prognosis. Recent decades have failed to witness a significant improvement in treatment outcomes for women with advanced disease, and mortality rates remain high. The precise role of surgical debulking, radiotherapy, hormonal therapy and cytotoxic chemotherapy in the treatment of advanced or recurrent disease is unclear. An improved understanding of the molecular pathology of endometrial cancer has allowed biologically relevant targets to be characterized and novel drugs are now being tested in early-Phase clinical trials. This review will present the evidence for the therapeutic options currently available to women with advanced or recurrent endometrial cancer and describe the progress that is being made in the field.